Branded Service Encounters: Strategically Aligning Employee Behavior with the Brand Positioning - Sirianni, Nancy J.; Bitner, Mary Jo; Brown, Stephen W.; Mandel, Naomi (Journal of Marketing, 2013)
This research examines how branded service encounters, in which frontline service employee behavior is aligned with a firm's brand positioning, may positively affect customer responses to brands. Across two brand personality contexts, Study 1 demonstrates that employee–brand alignment increases overall brand evaluations and customer-based brand equity, with more pronounced results for unfamiliar brands. Study 2 shows that conceptual fluency underlies the effect of employee–brand alignment on overall brand evaluations for unfamiliar brands. Study 3 reveals that employee authenticity enhances the effectiveness of employee–brand alignment. Finally, a critical incident study (Study 4) extends the generalizability of these findings to a wider variety of service contexts. This research is the first to demonstrate how firms can leverage employee behavior as a brand-building advantage, particularly for new or unfamiliar brands as they establish their positioning with customers.